Antibacterial Ti-Cu alloy with enhanced mechanical properties as implant applications - ChangBo Yi; ZunYun Ke; Lei Zhang; Jun Tan; YeHua Jiang; ZhengYuan He (Materials Research Express, 2020)
The service life as hard tissue implantation for clinical application needs compatible mechanical properties, e.g. strength, modulus, etc, and certain self-healing in case of internal infection. Therefore, for sake of improving the properties of Ti-Cu alloy, the microstructure, mechanical properties, corrosion resistance and antibacterial properties of Ti- x Cu alloy ( x  = 2, 5, 7 and 10 wt.%) prepared by Ar-arc melting followed by heat treatment were studied. The results show that the Ti-Cu alloy was mainly composed of α -Ti matrix and precipitated Ti _2 Cu phase. The Cu element mainly accumulates in the lamellar structure and forms the precipitated Ti _2 Cu phase. As the increase of Cu content, the lamellar Ti _2 Cu phase increases, the compressive strength and elastic modulus also were altered. The Ti-7Cu alloy exhibited the higher compressive strength (2169 MPa) and the lower elastic modulus (108 GPa) compared with other Ti-Cu alloys. The corrosion resistance of Ti- x Cu alloys increases with the increase of Cu content. When the Cu content was greater than 5 wt.%, the value of corrosion current density for Ti-Cu alloy was less than 1 μ A·cm ^−2 , which is also significantly lower than that of CP-Ti. The antibacterial test revealed that only the Ti-Cu alloy with 5 wt.% or greater Cu content could display a strong antibacterial rate against E. coli and S. aureus . Therefore, the prepared Ti-7Cu alloy via heat treatment showed excellent mechanical properties, corrosion resistance, and antibacterial properties, which would meet the replacement of human hard tissue and clinical applications.